Etika Dalam Praktik Akuntansi Keuangan - Hermanto Hermanto (STABN RADEN WIJAYA WONOGIRI, 2021)
ABSTRACT HERMANTO. Ethics in Financial Accounting Practices. This study aims to examine the theoretical study of ethics in financial accounting practice. The data used in this study is qualitative data about ethical violations in financial accounting practices that occurred at PT Tiga Pilar Sejahtera Food Tbk. From this data, a theoretical study was carried out with qualitative research methods for the theory applied or not by the entity. The results of this study indicate that PT Tiga Pilar Sejahtera Food Tbk committed ethical violations in the practice of financial accounting in the presentation of its financial statements. Keywords: Ethics, financial statements, financial accounting.